Blend Sign Is a Strong Predictor of the Extent of Early Hematoma Expansion in Spontaneous Intracerebral Hemorrhage - Zhang, Mingyue; Chen, Jie; Zhan, Chenyi; Liu, Jinjin; Chen, Qian; Xia, Tianyi; Zhang, Tingting; Zhu, Dongqin; Chen, Chao; Yang, Yunjun (Frontiers in Neurology, 2020)
Background and Purpose: We aimed to compare blend sign (BS) with other noncontrast computed tomography (NCCT) markers to predict the extent of hematoma expansion (EHE) in patients with spontaneous intracerebral hemorrhage (sICH). Methods: Patients with sICH who admitted to our Neurology Emergency Department from September 2013 to January 2019 were enrolled. The EHE was calculated as absolute increase of hematoma volume between baseline and follow-up CT (within 72 h). The EHE was also categorized into 4 groups: "no growth"; "minimal change (≤5.1ml)"; "moderate change (5.1-12.5ml)" and "massive change (>12.5ml)". Univariate and multivariate analyses were performed to investigate the relationship between NCCT markers (BS, black hole sign, satellite sign and island sign) and the EHE. Results: A total of 1111 sICH patients were included (median age, 60 years; 66.5% men). Multiple linear regression analysis showed that the presence of BS and black hole sign (BHS) were independently associated with the EHE after adjusting for confounders (P<0.001 and P=0.003, respectively). The presence of BS and BHS were positive correlated with growth category (r=0.285 versus r=0.199, P<0.001 for both). BS presented with a better predictive performance for the EHE compared with BHS (the area under the curve [AUC], 0.67 versus 0.57; P<0.001 for both). Conclusions: In patients with acute sICH, BS showed a better performance in predicting the EHE compared with other NCCT markers. This imaging marker can help with the identification of patients at high risk of significant expansion and may facilitate early management.